Nilai-nilai Universalitas Daâwah dalam al-Qurâan - Wahid, Abd. (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
This paper explores the universal principles of Islamic propagation (daâwah) according to the holy Qurâan. In doing this, the paper employs the thematic approach by collecting the Qurâanic verses that speak of daâwah, and interpret them analytically. Specific attention will be given to the verses that are rooted in the Arabic word daâa, which means âto callâ, and balagha, which means âto conveyâ. Other verses that have to do with the activity of daâwah will be touched briefly. The paper argues that the concepts of âcallingâ and âconveyingâ constitute the most important and central notion of daâwah in Islam. Together the two represent the holistic Islamic idea of not only spreading out Islam, but also of building a community based on religiosity. Islamic concept of daâwah is universal because it targets not only Muslim but also all human being based on understanding, tolerance and harmony.